SBAs, EMQs and SAQs in the Specialties - Hanks, Matthew (MedQ4exams Ser., 2021)
SBAs, EMQs & SAQs in the SPECIALTIES provides a broad range and style of questions, not only for medical students preparing for their final exams, but also for clinicians preparing for their postgraduate exams.